Aprendizagem baseada em projetos mediada pelo uso de WebQuest na formação inicial de professores de língua inglesa - MARTINS, Tania Cristina Silva (Universidade Federal do Pará, 2024)
The professional development of pre-service English language teachers plays a fundamental role in the context of contemporary Brazilian education, such as, for example, in preparing future teachers for the development of lifelong learning skills, namely, good communication, critical thinking, digital literacy, among others, just to name a few. Such teacher development can help the teacher to better identify, critically and reflectively, the needs and interests of students, and enable personalized learning, through each student's life projects. Therefore, this research aimed to present an educational process based on project-based learning (PBL), mediated by the use of WebQuest, for pre-service English language teachers. Grounded in the principles of the qualitative research approach and using the action research method, the educational process, entitled “WebQuest: project-based learning in English language teaching”, was planned, applied and evaluated in the context of the degree subject “Technologies in the teaching and learning of foreign languages”, in the English language teaching major, at the Faculty of Modern Foreign Languages (Faculdade de Letras Estrangeiras Modernas - FALEM), at the Federal University of Pará (Universidade Federal do Pará - UFPA). The results of the evaluation of the educational process demonstrate its effectiveness in contributing to the pre-service English language teachers' professional development, by creating conditions for meaningful learning about PBL, mediated by the potential of WebQuest, both as a technological resource and as a methodology. It should be noted that this educational process was evaluated by student-participants in the research and by expert teachers. Furthermore, by integrating PBL and WebQuest, the educational process gained aspects of innovation and replicability. It is concluded that this research can contribute to the advancement of knowledge in the field of study of PBL in the Brazilian context of teaching and learning the English language, with regard to curricular integration, teacher development and the incorporation of digital technologies in PBL.